Entorno familiar positivo y su incidencia en el rendimiento académico de un estudiante de la Unidad Educativa Quevedo - Ortiz Bejarano, Gabriela Stefania (2021)
The objective of this research was to analyze the level of impact of the positive family environment and its incidence on the academic performance of a student, projecting as a general objective to identify the influential benefits that families have on children and young people in educational processes, The methodological framework This research was theoretical, gathering vast information through the literature review of scientific articles, developing in depth the selected variables. As a result, the family bond positively influences school performance, taking into account that interpersonal relationships predominate in the emotional state of human beings, for this reason, emphasis is placed on this theme that will give priority to fusion parental family-school, in order to ensure a quality education despite the difficulties and uncertainty in which society finds itself. Consequently, it is concluded that the effectiveness of the relationship that must exist between the family and the educational system will give relevant results for a sustainable and proactive society in order to achieve and guarantee notable changes in the academic performance of a student. An adequate family climate enhances the behavioral and psychological level of the sons and daughters.